High-order-harmonic spectra from atoms in intense laser fields: Exact versus approximate methods - Pugliese, Silvina Norma; Simonsen, A. S.; Førre, M.; Hansen, J. P. (American Physical Society, 2015)
Fil: Pugliese, Silvina Norma. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina